DataCite - A global registration agency for research data - Jan Brase (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2010)
Since 2005, the German National Library of Science and Technology (TIB) has offered a successful Digital Object Identifier (DOI) registration service for persistent identification of research data. In 2009, TIB, the British Library, the Library of the ETH Zurich, the French Institute for Scientific and Technical Information (INIST), the Technical Information Center of Denmark, Canada Institute for Scientific and Technical Information (CISTI) the Australian National Data Service (ANDS) and the Dutch TU Delft Library all signed a Memorandum of Understanding to improve access to research data on the internet. The goal of this cooperation is to establish a not-for-profit agency called DataCite that enables organisations to register research datasets and assign persistent identifiers to them, so that research datasets can be handled as independent, citable, unique scientific objects.
Keywords: 330; Persistent Identifier; Research Data